Efforts to Combating Terrorism in Indonesia - Wida Azlina; Yasmirah Mandasari Saragih; Tamaulina Br. Sembiring; Widya Meilani; Yoldy Israq; Zahrana Syavica (International Journal of Sociology and Law, 2025)
Indonesia needs get rid of terrorism For forever . Journal This aiming For describe and analyze with use approach various effort countermeasures crime terrorism in Indonesia. Methods research used​ in study This use approach qualitative descriptive For serve description about terrorism and some strategy For to fight crime This is in Indonesia. Formulation problem based on description background back on top is as following : what just factor crime terrorism in Indonesia and how method overcome crime terrorism in Indonesia. Terrorism is disturbing phenomenon . Efforts​ countermeasures crime terrorism committed​ Government implemented through effort repressive . There are five factors that cause crime terrorism in Indonesia, namely : ethnicity , nationalism / separatism , poverty and inequality and globalization , non-democracy , violations dignity humans and religious radicalism .